Influence of Different Catalytic Metals on the Formation of PCDD/Fs during Co-combustion of Sewage Sludge and Coal - Xiaoqing Lin; Tieying Mao; Yunfeng Ma; Xiangbo Zou; Lijun Liu; Wenhua Yin; Mumin Rao; Ji Ye; Chuangting Chen; Hong Yu; Xiaodong Li; Jianhua Yan (Aerosol and Air Quality Research)
Abstract Co-combustion of sewage sludge (SS) and coal was developed rapidly in China, however, less attention was paid to the formation characteristics of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) and the influence factors, such as the catalytic metals (CuCl2, FeCl3, ZnCl2, CuO, Fe2O3, and ZnO), sources of carbon and chlorine. During the co-combustion of SS (2.5 wt.%) and coal (97.5 wt.%), the formation content of PCDD/Fs was 0.51 ng g–1 and 0.01 ng I-TEQ g–1. By adding metal chlorides (2.0 wt.% CuCl2, FeCl3, and ZnCl2), the formation contents of PCDD/Fs were increased significantly to 148.99, 67.38, and 53.63 ng g–1 (i.e., 2.10, 1.09, and 1.34 ng I-TEQ g–1), respectively, while the metal oxides (2.0 wt.% CuO, Fe2O3, and ZnO) only increased the PCDD/F contents to 1.27, 0.76, and 0.57 ng g–1 (0.03, 0.01, and 0.02 ng I-TEQ g–1), respectively. That is, the promotion effect of different metal additives on PCDD/F formation followed a sequence of CuCl2 (292×) > FeCl3 (132×) > ZnCl2 (105×) ≫ CuO (2.5×) > Fe2O3 (1.5×) > ZnO (1.1×), wherein the metal chlorides showed 2 orders of magnitude higher promotion than that of metal oxides. The proportion of highly chlorinated PCDD/Fs was further increased after adding metal chlorides, while the additional metal oxides decreased it. The de novo synthesis was revealed as the major formation pathway of PCDD/Fs except for adding ZnO. The CuCl2 and FeCl3 can also enhance the chlorination routes to generate PCDD/Fs. Only ZnO showed the promotion effect on the CP-route. The chlorine source was an essential limiting factor for generating PCDD/Fs, and the chlorine from metal chlorides was the preference source compared with that contained in SS and coal. The results have important reference value for controlling PCDD/Fs formation in the co-combustion process of SS and coal.